PENDAMPINGAN PROGRAM KEJAR MUTU PEMBELAJARAN LITERASI DAN NUMERASI PASCA PANDEMIC DI SDN 5 KARANGAMPEL - Zakiyah Ismuwardani; Ratri Nuryani Qudwatullathifah (LPPM Universitas Bina Bangsa, 2022)
The COVID-19 pandemic has had a prolonged negative social impact on the education sector. Where there are problems dropping out of school, decreased learning achievement, and violence against children. Based on data in the field, the impact of Covid-19 also causes the loss of literacy and numeracy, so it is necessary to hold a mentoring program to overcome the loss of motivation and the loss of participants in learning. Indramayu Regency as one of the regions that is at level 3 and according to the Ministry of Home Affairs Number 30 of 2021 has been able to carry out face-to-face learning. The implementation of literacy and numeracy learning provides solutions ranging from reflection to follow-up plans. The steps in this program include: (1) technical guidance and coordination activities; (2) preparation of work plans and development of numeracy literacy instruments; (3) preparation of guidebooks and modules as well as coordination with schools. The results of the analysis of the initial and final assessments of students, teachers, and parents at SDN 5 Karangampel showed that the program was implemented well with data that 98% of students felt enthusiastic and happy to participate in literacy and numeracy mentoring activities through the establishment of a progressive matching environment